Description of three new species of the tropical Asian jumping spider genus Onomastus Simon, 1900 from high altitude cloud forests of Sri Lanka (Araneae: Salticidae) - Benjamin, Suresh P.; Kanesharatnam, Nilani (Zootaxa, 2016)
Spiders of the tropical Asian jumping spider genus Onomastus Simon, 1900 are small to medium-sized, delicate, translucent, commonly found inhabitants of Asian evergreen forest foliage. In this paper, three new species of the genus, O. jamestaylori sp. nov. (♂♀), O. corbetensis sp. nov. (♂♀) and O. maskeliya sp. nov. (♂♀) are described from Sri Lanka. The three new species are added to the matrix of a previous study to assess their phylogenetic position. The resulting cladistic analysis, based on 35 morphological characters from 18 taxa (13 Onomastus species and 5 outgroups) supports the monophyly of the genus. Additionally, a monophyletic, well-supported South Asian clade (India, Sri Lanka), which is restricted to the Sri Lanka-Western Ghats biodiversity hotspot, is recovered in most analysis. The three newly described species might be endangered due to their small population size and restricted distribution in high altitude cloud forest.